2021
DOI: 10.1007/s12062-021-09352-4
|View full text |Cite
|
Sign up to set email alerts
|

Older People in Germany During the COVID-19 Pandemic:The Least, the More, and the Most Affected

Abstract: Older people have been identified as a particularly vulnerable group during the COVID-19 pandemic. However, the question of how older people actually fared during the COVID-19 pandemic has only been sporadically addressed. This article aims to partly fill this gap by classifying subgroups of older people using Latent Class Analysis. Indicators used are: risk perception, safety behavior, and well-being. To predict subgroup membership, age, gender, living arrangement, children, chronic illness, conflict, socioec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Other studies have investigated the COVID-9 pandemic impact in terms of concerns and anxiety 51 or perceived risk and preventive behavior. 52 , 53 Similarly, to our study, they used the LCA and found an increasing level of COVID-19 impact among different classes, for example Horn and colleagues 52 identified three subgroups: the least, the more and the most affected by the COVID-19 pandemic. However, these studies were conducted on specific sub-groups, university students, 51 older adults 52 and social media users 53 while our study concerns the general population.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Other studies have investigated the COVID-9 pandemic impact in terms of concerns and anxiety 51 or perceived risk and preventive behavior. 52 , 53 Similarly, to our study, they used the LCA and found an increasing level of COVID-19 impact among different classes, for example Horn and colleagues 52 identified three subgroups: the least, the more and the most affected by the COVID-19 pandemic. However, these studies were conducted on specific sub-groups, university students, 51 older adults 52 and social media users 53 while our study concerns the general population.…”
Section: Discussionsupporting
confidence: 64%
“…Other studies reported an association between female gender and increased psychological distress caused by the pandemic. 51 , 52 , 54 , 55 This result may be related to higher fear and anxiety responses of women related to a perceived higher vulnerability along with an increased risk of developing post-traumatic symptoms as compared to men. 55–58 Similarly, the association between young age, low-income and greater psychological impact of the pandemic is consistent with evidence from other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower SES groups and older adults with disabilities or diseases may be more likely to be affected, resulting in an underestimation of associations. It should be considered that the impact of the COVID-19 pandemic may have worsened the HRQOL of older adults, which is likely to affect socially disadvantaged older adults in particular [ 17 ] . We assume specification errors in our empirical model affect model validity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies also indicate that risk perception and worry decrease with increasing age 29 . Older men show a lower perception of risk and are less inclined to implement changes in their health behaviour than women and young people 24 .…”
Section: Discussionmentioning
confidence: 99%